HARAPAN MAHASISWA KEPERAWATAN TERHADAP PENAMPILAN DOSEN-DOSEN DI PROGRAM KEPERAWATAN - Monica Kartini; Ermayani Putriyanti (STIKES Ngesti Waluyo, 2021)
Background: Assessing what students expect of their teachers may provide some insight for teachers about what performances that are expected from them and a base to enhance their teaching performance. The study was conducted in two YAKKUM nursing schools, which have two entry levels for students, those graduated from senior high school and upgrading students. Objectives: The study aimed to identify the expectations of nursing students about the performance of their teachers and determine if there was a difference in expectations between students who graduated from senior high school and upgrading students. Methods: This research is a descriptive exploratory study using a survey questionnaire. The questionnaire consisted of five categories each with a variety of question and one open-ended question. The quantitative data was analyzed using descriptive statistics, while the qualitative data used thematic analysis. Result: All five categories of quantitative data rendered mean values of 3 or more. They were teaching preparation and procedures (mean=3.12), classroom management (3.11), knowledge of subject (mean=3.37), personal characteristics (mean=3.12), and interpersonal characteristics (mean=3.08). Conclusion: In summary, students had a high expectation of five categories of teachers’ performances, with knowledge of subject as the most expected performances. There was one category, interpersonal characteristics, that was significantly different between the two types of respondents.